RETRACTED: Non-Surgical Removal of Basal Cell Carcinoma by Apis Mellifera L Venom - Ahmed Kamal Samia (Journal of Skin Cancer Epidemiology, 2020)
This article has been retracted on March 01, 2021. VIEW THE RETRACTION NOTICE (https://openaccesspub.org/jsce/article/2243) Background Apis Mellifera L venom (Honeybees) is potent and safe anticancer drug. The present case is Basal Cell Carcinoma (SBCC), recurrent and invasde the skin of head (upper right, in front of the right ear). The patient was 65 years old in time of first intervention and the origin of BCC was primarily seen as abnormal growths and changes in birth mole on right side of head. Materials & Methods Preparation Bee Venom solution: Bee venom powder (crude) of dose 1gm was dissolved in 1000 ml of sterile distilled water then filtered by 0.22 micron syring filter. That final concentration of the stock bee venom become 1 ug /ml (i.e. 1ul=1 ug), and kept at -20◦C. (1mg (dried BV) + 1ml (water) = Final concentration (1ug/1 ul)). Before this novel intervention, allergy test performed by subcutaneous injection of small dose of bee venom (0.1 ml) and wait for at least one hour. The patient was not hypersensitive to honeybees’ venom. First stage of treatment: 1- Syringe of 1ml volume was used for direct local injection of cancer area by 0.3 ml from prepared Honeybees venom (0.1 % conc.). 2- At the same time, subcutaneous injection of 0.5 ml of bee venom solution infiltrated around the affected ear. 3- Topical application of the bee venom ointment 2% (bee venom in Vaseline) inside affected ear to protect the ear drum. This process repeated daily with cleaning of the ear every time by suitable safe and sterile saline solutions. 2nd stage: daily S/C injection in axillary area upper lymph nodes of 0.3 ml / bee venom ‘total doses 0.6 ml BV’ (left & right). 3rd stage: bee venom dissolved in sterile Clove oil was applied on inner ear above the drum. 4th stage: Management of healing process was enhanced by ascorbic acid solution as topical application on dead cancer cells and to help in removal of exudates and debris. Results The complete removal of malignant growths in affected ear achieved after 1 month from first bee venom injections. However; the cancerous areas under the second surgical intervention were treated during the next month. Conclusions Apis Mellifera L venom as anticancer drug is totally different from using direct stings as a method of Apitherapy, that because collection of bee venom lead to evaporating of most allergic substance that present in bees stings, also it can be used per os in people who exhibit different degrees of allergy against the drug safely.
Keywords: skin basal cell carcinoma